PITX2 associates with PTIP-containing histone H3 lysine 4 methyltransferase complex - Liu, Yan (2014)
Pituitary homeobox 2 (PITX2), a Paired-like homeodomain transcription factor and a downstream effector of Wnt/β-catenin signaling, plays substantial roles in embryonic development and human disorders. The mechanism of its functions, however, is not fully understood. In this study, we demonstrated that PITX2 associated with histone H3 lysine 4 (H3K4) methyltransferase (HKMT) mixed-lineage leukemia 4 (MLL4/KMT2D), Pax transactivation domain-interacting protein (PTIP), and other H3K4 HKMT core subunits. This association of PITX2 with H3K4 HKMT complex was dependent on PITX2’s homeodomain. Consistently, the PITX2 protein complex was shown to possess H3K4 HKMT activity. Furthermore, the chromatin immunoprecipitation result revealed co-occupancy of PITX2 and PTIP on the promoter of the PITX2’s transcriptional target. Taken together, our data provide new mechanistic perspectives on PITX2’s functions and its related biological processes.